Quantifying child directed speech cross-culturally across development - Bunce, John (2019)
Child-directed speech (CDS) influences language development (e.g., Golinkoff et al., 2015), but varies across cultural and demographic groups (Hoff, 2006). Recent work examining speech heard by North American English (NAE) infants found an increased proportion of CDS with age (Bergelson et al., 2018). Quantity of CDS remained relatively constant across age, while quantity of adult-directed speech (ADS) decreased. We replicate these findings using a different methodology, and expand them to include other language communities. Our data come from daylong audio recordings of 58 children ages 2?36 months from the ACLEW dataset (Bergelson et al., 2017; 30 children acquiring NAE, 10 UK English, 8 Argentinian Spanish, and 10 Tseltal/Mayan). Ten randomly selected 2-min segments (Tseltal: nine 5-min segments) from each child were annotated for speaker gender, age (child or adult), and addressee for each utterance. We calculated the minutes per hour of CDS, ADS, and all speech. Preliminary analyses find high variability in overall language input across individuals, age, and culture, and partially replicate the Bergelson et al. (2018) pattern of results. Ongoing annotation will permit finer-grained analyses of sub-group differences. Further analyses will examine the influence of factors such as speaker gender, number of speakers, and maternal education.